2017
DOI: 10.1177/0739532917722984
|View full text |Cite
|
Sign up to set email alerts
|

Friendships sustain volunteer newspaper for 21 years

Abstract: After the community of Almena, Kansas, lost its newspaper, citizens formed an all-volunteer organization to publish the hyperlocal Prairie Dog Press, which has existed for 21 years. This study examines the dynamics of the organization and volunteers’ motivations and finds collective efficacy and civic engagement at least partially explain the organization’s longevity. Volunteers’ strong bonds with one another have been key to sustaining the newspaper’s production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Friendship opportunities in organizations have direct effects on job involvement and job satisfaction and indirect effects on organizational commitment and turnover intention (Riordan & Griffeth, 1995), and workplace friendship mediates the relationship of ethical leadership to task performance (Liu, Kwan, Fu, & Mao, 2013). Volunteers' strong friendship is critical to sustaining a defunct newspaper's production for 21 years (Smethers, Bressers, & Mwangi, 2017). Opportunities exist for research on workplace friendship on the acquisition and retention of employees, and its influence on the task and contextual performances.…”
Section: Contribution To Knowledgementioning
confidence: 99%
“…Friendship opportunities in organizations have direct effects on job involvement and job satisfaction and indirect effects on organizational commitment and turnover intention (Riordan & Griffeth, 1995), and workplace friendship mediates the relationship of ethical leadership to task performance (Liu, Kwan, Fu, & Mao, 2013). Volunteers' strong friendship is critical to sustaining a defunct newspaper's production for 21 years (Smethers, Bressers, & Mwangi, 2017). Opportunities exist for research on workplace friendship on the acquisition and retention of employees, and its influence on the task and contextual performances.…”
Section: Contribution To Knowledgementioning
confidence: 99%
“…The Humboldt experience echoes Almena, Kansas, where the Almena Plaindealer ceased publication after 102 years of service. A survey of 400 people in the tiny town found that former Plaindealer readers missed similar types of local news and attempts by other area media failed to provide adequate coverage (Smethers, et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other communities, volunteers have banded together after a newspaper closed to create a news publication. Research into a volunteer-run newspaper in Kansas showed that there were social benefits both for the volunteers who created the newspaper and for the larger community itself (Smethers et al, 2017).…”
Section: Alternative News Production Systemsmentioning
confidence: 99%
“…Moreover, news organizations are more likely to emerge in middle-and higher-income communities, while news outlets that close in low-income and more ethnically diverse communities are less often replaced (Napoli et al, 2017). The financial sustainability of non-profit media models has also been raised as a concern (Konieczna & Robinson, 2014), and volunteer-run newspapers often rely on a small group of dedicated individuals, relying on effective leadership to be successful (Smethers et al, 2017). Finally, the quality of information produced by digital news organizations has been described as significantly lower than traditional news outlets (Darr et al, 2018).…”
Section: Alternative News Production Systemsmentioning
confidence: 99%